Analysis of Teacher Performance Management in Increasing Student Motivation at MAN 1 Langkat: In the New Normal Era - Novita Sari; Ahmad Mukhlasin; Safitri Safitri (Pusdikra-Publishing.com, 2023)
Activities in the world of education are gradually returning to normal. Madrasah institutions' readiness for face-to-face learning requires compliance with Health protocols. The role of the teacher is as a way of guiding, motivating and guiding all elements of students in a group to obtain the expected goals and enable the teacher's performance to run optimally. The aim of this research is to determine teacher performance in increasing MAN Langkat students' learning motivation in the New Normal Era. This research uses qualitative research, with a descriptive qualitative research type. The research subjects were teachers and students of Madrasah Aliyah Negeri 1 Langkat. Data collection techniques use interviews, observation and documentation. The research results aim to determine the obstacles found by teachers at MAN 1 Langkat in increasing student learning motivation in the new normal era. The results of this research show that the efforts implemented by teachers to motivate student learning in the new normal era are: by instilling disciplinary behavior and the importance of communication to students, and limiting the use of e-digital media in learning.